2009
DOI: 10.2139/ssrn.1427794
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between Direct and Securitized Real Estate

Abstract: Using data for the 1978-2008 period, this study presents evidence for cointegration between securitized (NAREIT) and direct (NCREIF) total return indices. Cointegration between the indices indicates that REITs and direct real estate are substitutable in the portfolio of a longhorizon buy-and-hold investor. Since the real estate indices are not found to be cointegrated with the stock market, REITs and direct real estate are likely to have similar long-term diversification benefits in a stock portfolio. In line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 39 publications
5
32
0
3
Order By: Relevance
“…REITs behave more like real estate in strong economic conditions than in bad. In the research by Oikarinen et al (2011), evidence shows correlation between both returns of securitized and direct real estate approach 1 in the long run, which is consistent with our results. …”
Section: Research Methodology Empirical Results and Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…REITs behave more like real estate in strong economic conditions than in bad. In the research by Oikarinen et al (2011), evidence shows correlation between both returns of securitized and direct real estate approach 1 in the long run, which is consistent with our results. …”
Section: Research Methodology Empirical Results and Analysissupporting
confidence: 92%
“…However, some studies have documented that over long horizons the linkages between indirect and direct real estate are quite strong (Giliberto, 1990;Seck, 1996;Ziering et al, 1997;Geltner and Kluger, 1998;Seiler et al, 2001;Mackinnon and Zaman, 2009;Oikarinen et al, 2011;Hoesli and Oikarinen, 2012). The study of Hoesli and Oikarinen (2012) shows that long-run REIT market performance is much more like the direct real estate market than the general stock market, while the short term comovement between REITs and stocks is stronger than that between REITs and direct real estate We use the Panel Smooth Transition Regression (PSTR) model, which was recently developed by Gonzàlez et al (2005) to set 3-month interest rate change as threshold variables, and to determine the relative influence of stock, fixed-income securities and direct real estate to Japan and the U.S. REITs as a whole in different regimes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The same trend was also evident in the study by Oikarinen et al (2011) in which it was found that returns on the US REIT market since 1990 have led the US direct market returns when appraisal or valuation-based indices are used as proxies for direct market returns.…”
Section: Relationships Since 1990supporting
confidence: 62%
“…For instance, Oikarinen et al (2011) examined the long-run relationship between the US-based NAREIT and NCREIF indices during the period 1977-2008 and found evidence of co-integration between the two return series, whereas no co-integration effect was evident between the listed real estate and stock market returns. This confirms the findings of a study by Pagliari et al (2005) in which returns were adjusted for the impact of appraisal smoothing, leverage and differences in sector composition, and no notable difference was found between the return means and variance of the NCREIF and NAREIT indices between 1993 and 2001.…”
Section: The Long-term Relationshipmentioning
confidence: 99%
“…Mueller and Mueller, 2009). On the other hand, there is also empirical evidence that the direct and public real estate returns are cointegrated, suggesting that in the long run direct and public real estate investments can be regarded as substitutes in a mixed asset portfolio (Pagliari et al, 2005;Oikarinen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%